ASSESSING THE RECORD AND CAUSES OF LATE TRIASSIC EXTINCTIONS - Tanner L.H.; Lucas S.G.; Chapman M.G. (My University, 2004)
Accelerated biotic turnover during the Late Triassic has led to the perception of an end-Triassic mass extinction event, now regarded as one of the ‘‘big five’’ extinctions. Close examination of the fossil record reveals that many groups thought to be affected severely by this event, such as ammonoids, bivalves and conodonts, instead were in decline throughout the Late Triassic, and that other groups were relatively unaffected or subject to only regional effects. Explanations for the biotic turnover have included both gradualistic and catastrophic mechanisms. Regression during the Rhaetian, with consequent habitat loss, is compatible with the disappearance of some marine faunal groups, but may be regional, not global in scale, and cannot explain apparent synchronous decline in the terrestrial realm. Gradual, widespread aridification of the Pangaean supercontinent could explain a decline in terrestrial diversity during the Late Triassic. Although evidence for an impact precisely at the boundary is lacking, the presence of impact structures with Late Triassic ages suggests the possibility of bolide impact-induced environmental degradation prior to the end-Triassic. Widespread eruptions of flood basalts of the Central Atlantic Magmatic Province (CAMP) were synchronous with or slightly postdate the system boundary; emissions of CO2 and SO2 during these eruptions were substantial, but the contradictory evidence for the environmental effects of outgassing of these lavas remains to be resolved. A substantial excursion in the marine carbon-isotope record of both carbonate and organic matter suggests a significant disturbance of the global carbon cycle at the system boundary. Release of methane hydrates from seafloor sediments is a possible cause for this isotope excursion, although the triggering mechanism and climatic effects of such a release remain uncertain.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая